BINTIK CATU - Liek Wilardjo (Techné : Jurnal Ilmiah Elektroteknika, 2012)
One-dimensional square potential well is used as a model for quantum dots. Its Schroedinger's equations and their solutions both eigenstates and eigenenergies for he lowest three levels are explained qualitatively and derived mathematically.